ENERGY-EFFICIENT REGIMES FOR HEATING-SUPPLY OF THE RESIDENTIAL BUILDINGS - S. N. Osipov; V. M. Pilipenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
Rise in comfort and inhabitation safety is one of the main requirements of the general maintenance, reconstruction of the old and construction of the new residential houses. One of the essential factors of it is substitution in the household hot-water preparing sources: from the individual domestic gas  water-heaters to  the common  entire-building hot-water supply at the expense of the centralized heat supply. Extremely erratic hot-water daily consumption by tenants leads to the necessity of sharp increase in central heat-supply level during a few hours of the day, which requires a significant increase of the source heat-power. On that score, the authors propose to direct a significant part (up to 50 %) of the centralized heating and ventilation heat power-consumption to the hot water preparation during the period of short-term hot water consumption peak.Substitution  of  the  individual  domestic  gas  water-heaters  with  the  common  entirebuilding hot-water supply releases a huge amount of natural gas which can be utilized not only for production of the necessary heat power but as well for electric power producing. This substitution is especially advantageous if heat-power is delivered to the residential area from a НРС where significant part of heat especially in a relatively warm season of the year is thrown out into the air. The content of the article is based on several patents received earlier.